2018
DOI: 10.1021/acs.jpcc.8b03551
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Environmentally Relevant Physicochemical Conditions on a Highly Efficient Inorganic Ice Nucleating Particle

Abstract: Ice nucleation microphysical processes are identified to be of high importance in forecasting the magnitude of the Earth’s climate change. The environmental conditions often influence the ice nucleation processes in the Earth’s atmosphere. We herein study the impact of various environmental conditions on FeHg (maghemite–Hg2Cl2 composite), a highly efficient ice nucleating particle with similar freezing point to the best inorganic ice nuclei, AgI. FeHg is formed from FeCl2·4H2O and HgCl2, which are observed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 88 publications
0
18
0
Order By: Relevance
“…There are rarely any reports so far for heterogeneous ice nucleation in the immersion mode of ZnO. We reported previously that ZnO reduced INE of purely inorganic and environmentally available ice nucleating particles. In this study, we found that plastic nano- and microparticles decreased the INE of ZnO.…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…There are rarely any reports so far for heterogeneous ice nucleation in the immersion mode of ZnO. We reported previously that ZnO reduced INE of purely inorganic and environmentally available ice nucleating particles. In this study, we found that plastic nano- and microparticles decreased the INE of ZnO.…”
Section: Resultsmentioning
confidence: 84%
“…Electron microscopy imaging did not indicate the roughness of the plastic particles. Therefore, it is likely that a mechanism related to the low lattice mismatch between ice and plastic particles is attributed to enhancement of INE. , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kaolin contaminated with CuCl 2 was a highly efficient adsorbent, able to take up gaseous elemental Hg within seconds at room temperature (16.33 mg g −1 of Cu from inductively coupled plasma mass spectrometry analysis). Previously, we synthesized Fe composite BHFe from the reduction of FeCl 2 by NaBH 4 followed by aerial oxidation. BHFe is an efficient Hg II adsorbent and produced a highly efficient ice‐nucleating particle HgBHFe (maghemite@Hg 2 Cl 2 ) after the uptake of HgCl 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Microphysics of ice nucleation to obtain furtherinsightso n potential reaction mechanism(s) Kaolin contaminated with CuCl 2 was ah ighly efficient adsorbent, able to take up gaseous elemental Hg within seconds at room temperature (16.33 mg g À1 of Cu from inductively coupled plasma mass spectrometry analysis). Previously, [27,28] we synthesized Fe composite BHFe from the reductiono fF eCl 2 by NaBH 4 followed by aerial oxidation. BHFe is an efficient Hg II adsorbenta nd produced ah ighly efficient ice-nucleating particle HgBHFe (maghemite@Hg 2 Cl 2 )a fter the uptake of HgCl 2 .I th as www.chemsuschem.org thus been shown that ionic Hg (in associationw ith Cl À )e nhanced the ice nucleation efficiency of BHFe significantly.…”
Section: Effect Of Selectedsalts and Halides On Hg 0 Adsorptiono N Kamentioning
confidence: 99%